(untitled) (Research, Society and Development, 2022)
The Amazon forest has a high diversity of Non-Timber Forest Products, which provide considerable support to local communities through food, medicines, plants of cultural importance, material for shelter and as a source of income, the sustainable exploitation of these products can contribute to the development of the region and for the well-being of the populations that depend on these resources for their survival, in addition, they are important products for the development of the bioeconomy in the Amazon. Exudates are among these products and can be of great economic, social and cultural value. The objective of this work was to identify, characterize the current state of information available for a series of species and discuss the potential use for different types of exudates. Using literature review as a methodology. As for the type, they can be classified as resin, latex, gum and sap. Its main uses are in folk medicine, food and cosmetics. They are found in abundance in the forests and have several potentialities, requiring more scientific studies to direct their exploitation in a sustainable way and bring economic return mainly to the traditional populations that inhabit these regions.